2017
DOI: 10.5897/jphe2016.0905
|View full text |Cite
|
Sign up to set email alerts
|

Risky sexual behavior and associated factors among youth in Haramaya Secondary and Preparatory School, East Ethiopia, 2015

Abstract: World Health Organization (WHO) defines "youths" as age group of 15 to 24 years, and are characterized by significant physiological, psychological and social changes that place their life at high risk. Youth who initiate sexual activity earlier get exposed to risks such as sexually transmitted diseases and unwanted pregnancy, at a time when their developmental status places them at a disadvantage in the assessment and management of these risks. The objective of this research was to assess the prevalence and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Thus, there is no significant association value of age, gender in this study, but there is a significant association with sociological factors such as consumption of tobacco and being drunk at (P=0.000) and (0.047) respectively. Also, a study carried out by Hirbo and Addisu [15] found that risky sexual behaviours among youths were substance use before sexual intercourse, watching pornographic movie, age at sex doubt. Similarly, this study identified a significant association between going to night clubs, visiting pornographic sites with (p=0.001), and watching pornographic videos with (p=0.003), OR 2.313 (1.192-4.486 were connected with early sexual initiation which are risky sexual behaviours among the respondents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is no significant association value of age, gender in this study, but there is a significant association with sociological factors such as consumption of tobacco and being drunk at (P=0.000) and (0.047) respectively. Also, a study carried out by Hirbo and Addisu [15] found that risky sexual behaviours among youths were substance use before sexual intercourse, watching pornographic movie, age at sex doubt. Similarly, this study identified a significant association between going to night clubs, visiting pornographic sites with (p=0.001), and watching pornographic videos with (p=0.003), OR 2.313 (1.192-4.486 were connected with early sexual initiation which are risky sexual behaviours among the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…It was a descriptive cross-sectional study. The study population was youths, 15 -24 years of age [9], who reside in Obi-Akpor and Ikwerre Local Government Areas. The inclusion criteria were; males and females aged between 15 and 24 years, and must have lived in Obio-Akpor and Ikwerre Local Government Areas for at least one year, while unmarried youths aged 15-24 years that were pregnant during this research were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] There are some studies about risky sexual behavior studies in Ethiopia, but, almost all targeted adolescents. [16][17][18][19][20][21][22] Nevertheless, evidence in Ethiopia showed that as men's age advances, the probability of them participating in risky sexual behavior also rises. For instance, the likelihood of having multiple sexual partners was eightfold greater among men aged 40-49 years compared to those aged 15-19 years.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented that risky sexual behavior has been associated with exposure to sexually explicit media, including pornography. 18,22,29 However, they may use condoms consistently, which this study did not investigate because the main source of data captured only condom use in the most recent sexual partner, which does not reflect continuous condom use. 28 HIV/AIDS -Research and Palliative Care 2023:15 https://doi.org/10.2147/HIV.S426379…”
mentioning
confidence: 99%